Activation of Bovine Plasminogen by the Plasminogen Activator in Animal Tissue - Abe, Takeshi; Astrup, Tage (Thrombosis and Haemostasis, 1960)
1. The activation of bovine plasminogen by means of the plasminogen activator from pig heart tissue has been studied on heated fibrin and on casein.2. Small, but varying, amounts of activator can be extracted from crude activator powder during the experiment and interfere therefore with estimations on normal, plasminogen containing fibrin.3. The activation process is a slow process. Results obtained on heated fibrin or casein suggest that the activation is caused by a stoicheiometric reaction.